Measurement Issues of Financial Placement and Technical Provisions of Czech Insurance Companies - Jiřina Bokšová (European Financial and Accounting Journal, 2011)
Measurement represents one of the most important methodological elements of accounting because it affects the overall informative ability of financial statements. The chosen method of valuation affects not only the amount of assets and liabilities, but the size of costs and revenues of the entity as well; therefore it has a major impact on profit and solvency of insurance companies. Each accounting regulation – whether at national or supranational level – includes relatively thorough provisions related to valuation. In the Czech accounting system valuation is regulated by the Accounting law, which distinguishes between the initial valuation of assets and liabilities (valuation at the transaction date) and the subsequent valuation of assets and liabilities “at the end of the reporting date”. However, the Czech definition of fair value at the national level is different from IFRS at the supranational level, which causes issues with reporting assets and liabilities of insurance companies. By 2015, a new IFRS is expected to be issued, dealing with insurance reporting issues, including “fair value”. This new standard is expected to address current deficiencies in insurance reporting guidance.
Keywords: G22; M41; 650; Insurance; Financial placement; Technical reserves; Historical cost; Fair value